Ecological risk assessment of microplastics and heavy metals in Northern Vietnam's estuarine sediments: A case study of Ba Lat and Bach Dang - Pham Thi Minh, Hanh; Le Thi, Huong; Le Thi Hong, Van; Truong Manh, Chien; Dang The, Ba; Dinh Hai, Ngoc; Duong Thanh, Nghi; Doan Thi, Oanh; Le Thi Phuong, Quynh; Nguyen Trung, Kien; Dang Anh, Tien; Duong Thi, Thuy (Vietnam Journal of Earth Sciences, 2025)
Estuarine environments are highly productive and biodiverse ecosystems that are particularly vulnerable to environmental pollution. This study assessed the presence and ecological risks of microplastics (MPs) and ten heavy metals in surface sediments from two major estuaries of the Red-Thai Binh River system in northern Vietnam: Ba Lat and Bach Dang. Sediment samples were collected during the rainy season (July 2024) under low tide conditions. The average concentrations of heavy metals followed the order: Hg < Cd < As < Ni < Cu < Cr < Pb < Zn < Mn < Fe. While most metal concentrations, except for Fe, were below Vietnamese regulatory limits (QCVN 43:2025/BTNMT), several samples exceeded the U.S. EPA (1997) Threshold Effects Level (TEL), particularly for As, Pb, Hg, Cu, and Ni. The geo-accumulation index identified Pb as the most enriched element, followed by As and Zn. Despite localized exceedances, the overall ecological risk associated with heavy metals was classified as low.In contrast, microplastic contamination posed a more prominent ecological threat. MP concentrations ranged from 3,600 to 9,000 items/kg (mean: 5,908±1,790) in Ba Lat and from 1,900 to 4,800 items/kg (mean: 3,858.3±832.8) in Bach Dang, surpassing levels reported in previous regional studies. The dominant particle types were small-sized fibers (< 2 mm) and fragments (0.05–0.2 mm²), which are likely to have greater bioavailability and ecological impact. A Potential Ecological Risk Index (PERI), incorporating MP abundance, polymer types, and hazard scores, indicated high-to-dangerous risk levels in Bach Dang and medium-to-high risk levels in Ba Lat. These findings highlight the urgent need for effective mitigation strategies, including improved plastic waste management and routine MP monitoring, particularly in ecologically sensitive areas such as aquaculture zones, coastal habitats, and salt production sites.